Creative education & political systems their common effect on sustainable business attitudes. Issue 3 (November 2020) - Looser, S.; Mohr, S.
Abstract: There is a prima facie argument that those who are affected by a decision should have a say in that decision. In terms of intergenerational equity, as well as regarding the evolution and implementation of Transition Pathway Management agendas, this should coercively include young people. In general, their opinions do not have any platform, forum, etc., thus they are ignored and not pursued, as experts and specialists in relevant fields, often for good reasons, develop Transition Strategies. Given the socio-cultural context, approach to technology etc., 10 to 12-year-old people are likely to have very different notions of their specific future, and the way sustainability is evolving within this. This opens up the distinct possibility that (older) experts devise and shape transition pathways that hopefully deliver greater sustainability and less carbon-intensive lifestyles, but do so in a governance void and in a direction that those who are destined to live (in) these futures find it difficult to loosen – or at least share – the control over those processes. In short, not involving young people in the evolvement of Transition Pathways and their Management (TPaM) risks a governance deficit as well as an implementation challenge. To understand how young people, conceptualise their future within the wider theoretical framework of TPaM and the role of CSR in promoting sustainable lifestyles, 105 Swiss pupils, living in a quite good situated (i.e., geographically as well as financially), at ages between 10 and 12 were asked to write an essay about their future visions. The paper outlines these visions, the pupils' perception of the future, and evaluates the adopted solutions (i.e. pathways) by qualitative analyses. Moreover, the identified TPaM are discussed in several follow-up workshops with the pupils at the age of 12 regarding their implications for the private and public sectors, notably affecting behaviours of e.g., energy and food consumption, mobility, educational systems, family set-ups, etc. Contrary to perceptions about the fully connected lifestyles of modern pupils, the results show for instance, their worries or even apprehensibility about the rapid pace of technological change. Thus, they fear isolation and "not being able to keep up". Following this, creative educational concepts that foster the evolvement of TPaM, the identification of innovative new measures and practical implications are key drivers. They establish legitimacy so to discuss potential TPaM at several political and private levels. Further, they build an integrated part to engage young people (and experts) in the development of suitable pathways towards the attainment of their visions. This involves a viable theoretical framework that is strong and deeply anchored and, to some extent, a convergence between pathway components as well as hands-on drivers to induce change processes. Based on this framework's practical step-by-step-approach it is able – independent from whether the very beginning are future visions or the status quo – to avoid barriers or hindering preconditions, only because vision is the multi-level perspective. Such an approach might allow also a comparison of different pathways. Highlights: For the first time – in terms of intergenerational equity – the evolution and implementation of Transition Pathway Management agendas was conducted with 10-12-years pupils. SBy triangulating qualitative data, standard analyses methods, and software based "qualitative" findings, the objectivity, internal validity as well as reliability was trail blazingly enhanced. The youth's political involvement manifested in a spill-over effect. As result: "those affected will have a voice in decision determining their future".